HAEMATOLOGICAL CHANGES INDUCED BY STARVATION IN MINOR CARP, LABEO BOGA (HAM.) - GUPTA, KADAMBRI; RAINA, SHEETU; SACHAR, ANUPRIYA; GUPTA, KRISHMA (Journal of the Inland Fisheries Society of India, 2021)
The study deals with alteration in haematological parameters in response to stress induced by starvation in the minor carp, Labeo boga for an experimental period of 60 days. Changes in haematological values viz, total erythrocyte count (TEC), haemoglobin (Hb), haematocrit (Hct), mean corpuscular haemoglobin (MCH), mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), total leucocyte count (TLC), differential leucocyte count (DLC) and thrombocytes based on ten day intervals were investigated from starved fish and compared to fish fed on regular diet (control). The results suggested that a process of senescence takes place in the pre-existent RBCs and such cells are not replaced during starvation. After 60 days of starvation, L. boga had a significantly reduced TEC, Hct, Hb and calculated blood indices viz. MCH, MCHC except MCV, which exhibited a marked increase. TLC, DLC and thrombocytes showed a change parallel to the RBC dependent parameters.Key words: Starvation, haematological parameters, Labeo boga, senescence